2021
DOI: 10.1186/s12985-021-01611-2
|View full text |Cite
|
Sign up to set email alerts
|

The key amino acids of E protein involved in early flavivirus infection: viral entry

Abstract: Flaviviruses are enveloped viruses that infect multiple hosts. Envelope proteins are the outermost proteins in the structure of flaviviruses and mediate viral infection. Studies indicate that flaviviruses mainly use envelope proteins to bind to cell attachment receptors and endocytic receptors for the entry step. Here, we present current findings regarding key envelope protein amino acids that participate in the flavivirus early infection process. Among these sites, most are located in special positions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 145 publications
2
37
0
Order By: Relevance
“…The results of TEM and biomolecular interactions analysis indicated that Cur-CQDs would interact with the E protein S123/K312 on JEV particles and then inhibit viral infection. The ectodomain of the JEV E protein consists of three structural domains I, II, and III followed by a flexible stem region that is connected to the C-terminal transmembrane helix ( 63 , 64 , 65 ). Two residues, S123 and K312, located near domains II and III of the E protein, respectively, play an important role in viral entry ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of TEM and biomolecular interactions analysis indicated that Cur-CQDs would interact with the E protein S123/K312 on JEV particles and then inhibit viral infection. The ectodomain of the JEV E protein consists of three structural domains I, II, and III followed by a flexible stem region that is connected to the C-terminal transmembrane helix ( 63 , 64 , 65 ). Two residues, S123 and K312, located near domains II and III of the E protein, respectively, play an important role in viral entry ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ectodomain of the JEV E protein consists of three structural domains I, II, and III followed by a flexible stem region that is connected to the C-terminal transmembrane helix ( 63 , 64 , 65 ). Two residues, S123 and K312, located near domains II and III of the E protein, respectively, play an important role in viral entry ( 64 ). In a neutral environment, the E protein tends to remain on the surface of mature JEV virions in a prefused state ( 66 , 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, wild-type Asibi virus utilizes the classical, clathrin-mediated endocytosis pathway, while live-attenuated 17D vaccine virus has been shown to enter cells in a unique, clathrin-independent mechanism [ 17 ]. Following receptor-mediated endocytosis, the virion undergoes pH-mediated fusion with the endosomes, and the genome migrates to the endoplasmic reticulum (ER) [ 18 ]. The genome is translated and replicated, and the virions are assembled as they bud through the ER membrane.…”
Section: Virologymentioning
confidence: 99%
“…These latter are involved in virus replication and assembly, and the inhibition of the antiviral immune response [9]. Protein E contains three domains: Domain I, which represents the N-terminal portion and influences viral tropism; Domain II, which comprises the dimerisation region and the fusion loop, and Domain III with a binding function to membrane receptors [10,11]. The fusion loop (FL) is the most conserved region among Flavivirus and plays a role in the infection process.…”
Section: Introductionmentioning
confidence: 99%